Minerais estratégicos e críticos: Uma vis\~ao internacional e da política mineral brasileira - Fernando Ferreira De Castro; Carlos Cesar Peiter; Geraldo Sandoval Góes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
Mineral raw materials are at the base of economic activities at some stage of their production chains and will continue to be more and more in the future. Certain raw materials have specific features, because both the supply risk and their economic importance vary between countries or economic blocs, and have been defined as "critical" due to uncertainties in their markets. In view of the global relevance of mineral goods, the objective of this discussion text is to present the current overview of the different international policies on critical and/or strategic minerals, adopted in China, the United States, the European Union, the main world consumers, comparing it with the progress in Brazilian studies and policies until the recent definition of the first list of strategic minerals in Brazil. Finally, a case of Brazilian niobium will be presented briefly, a strategic raw material for Brazil and critical mineral internationally. The adopted qualitative methodology is part of an extensive bibliographical and documental review in the context of geopolitics of raw materials, in order to present an overview of evaluation models and preparation of lists of critical and strategic raw materials in use, thus pointing out methodological alternatives to guide national policies.
Keywords: L71; L72; 330; strategic minerals; critical raw materials; niobium; ST&I